2007
DOI: 10.1110/ps.062737507
|View full text |Cite
|
Sign up to set email alerts
|

Structural context for protein N‐glycosylation in bacteria: The structure of PEB3, an adhesin from Campylobacter jejuni

Abstract: Campylobacter jejuni is unusual among bacteria in possessing a eukaryotic-like system for N-linked protein glycosylation at Asn residues in sequons of the type Asp/Glu-Xaa-Asn-Xaa-Ser/Thr. However, little is known about the structural context of the glycosylated sequons, limiting the design of novel recombinant glycoproteins. To obtain more information on sequon structure, we have determined the crystal structure of the PEB3 (Cj0289c) dimer. PEB3 has the class II periplasmic-binding protein fold, with each mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…The acceptor region appears to partially adopt an unstable ␣-helix conformation and form random coils (327). These findings were confirmed experimentally via a crystal study of the PEB3 glycosylated adhesin (313). Three key glycosylated residues are well exposed at the surface, which makes them accessible to PglB even in the folded state of the protein.…”
Section: Protein Glycosylationmentioning
confidence: 64%
See 1 more Smart Citation
“…The acceptor region appears to partially adopt an unstable ␣-helix conformation and form random coils (327). These findings were confirmed experimentally via a crystal study of the PEB3 glycosylated adhesin (313). Three key glycosylated residues are well exposed at the surface, which makes them accessible to PglB even in the folded state of the protein.…”
Section: Protein Glycosylationmentioning
confidence: 64%
“…The only feature that seemed to be dispensable was the addition of the glucose branch of the heptasaccharide (307). Gradually, more evidence emerged on the presence of other N-glycosylated proteins in C. jejuni strains (mostly in strains 81-176 and NCTC 11168), confirming the general nature of the N-glycosylation process, i.e., targeting a range of proteins (5,306,(308)(309)(310)(311)(312)(313). In total, more than 60 glycoproteins have already been identified in C. jejuni (5,114,309,311).…”
Section: Protein Glycosylationmentioning
confidence: 96%
“…This indicates that the consensus sequence alone is not sufficient for Nglycosylation, but the spatial environment is also important. [29,36] For the bacterial Nglycosylation system it is proposed that the glycosylation sites are located in flexible parts of folded proteins. [29] Rangarajan and coworkers [36] elucidated the structure of PEB3, a glycosylated adhesin from C. jejuni, and showed that the glycosylation site is located within a surface-exposed loop joining two structural elements.…”
Section: Design Of An Sgse Neoglycoprotein Carrying a C Jejuni Heptamentioning
confidence: 99%
“…[29,36] For the bacterial Nglycosylation system it is proposed that the glycosylation sites are located in flexible parts of folded proteins. [29] Rangarajan and coworkers [36] elucidated the structure of PEB3, a glycosylated adhesin from C. jejuni, and showed that the glycosylation site is located within a surface-exposed loop joining two structural elements. While the tertiary structure of SgsE is unknown, secondary structure prediction using PSIPREDView [37] revealed that Thr 620 and Ser 794 are located in a loop between two protein strands, thereby fulfilling the general requirement for bacterial glycosylation.…”
Section: Design Of An Sgse Neoglycoprotein Carrying a C Jejuni Heptamentioning
confidence: 99%
“…According to its annotation Paa has a "substrate binding domain of LysR-type transcriptional regulators" suggesting a possible regulatory function of this protein. Similarly, despite a suggestion by Rangarajan et al [49] that PEB3 may functions as an adhesin, there are no published data confirming it. A role of PEB3 in transport of 3-phosphoglycerate was reported by Min et al [50] suggesting a possible dual function of this protein.…”
Section: Contradictory Datamentioning
confidence: 89%